Epidemiolgi Deskriptif Hipertensi di Puskesmas Arjasa Kabupaten Jember - Jessica Febe Immanuela; Adistha Eka Noveyani; Arfiani Meikalynda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Hypertension is generally considered as a multi-factorial disease caused by more than one specific factor. Approximately over one billion people worldwide suffer from hypertension, with an annual death rate of 9.4 million. The purpose of this research is to describe the distribution of hypertension according to person, place, and time in the working area of Puskesmas Arjasa in Jember district. The research type used is descriptive quantitative. The research was conducted at Puskesmas Arjasa in Jember district from January to February 2023. The population and sample in this research are all hypertension patients at Puskesmas Arjasa in 2022. The independent variables in this research are descriptive epidemiology with person, place, and time variables. While the dependent variable is the proportion of hypertension. Data analysis is in the form of descriptive statistics to determine the distribution of each variable being studied. Based on the analysis results, the highest frequency of hypertension patients was found among female population at 63.41%, those above 45 years of age at 76.91%, with complications of diabetes mellitus at 33.07%, those living in Arjasa Village at 27%, and patients in the month of August at 13.31%.